2020
DOI: 10.1177/1464420720952813
|View full text |Cite
|
Sign up to set email alerts
|

Drop-weight impact testing for the study of energy absorption in automobile crash boxes made of composite material

Abstract: There is an ever-increasing demand in the automotive sector to continuously improve the performance and reduce cost through weight reduction in the structure of the vehicle. In the present scenario, it is also necessary to meet the standards set by crash safety regulating authorities in various parts of the world. In automobiles, the crash box is placed in the anterior region to absorb the impact energy in the event of an accident. Glass fiber reinforced plastic crash boxes have a high strength-to-weight ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Results showed that when compared with the conventional crash box, the proposed optimal design leads to great improvement on account of not only the energy absorption per unit mass, but also the initial peak force. Through adopting drop-weight impact testing, Hussain et al 2 investigated the effectiveness of disparate triggers in combination with different geometries for glass fiber reinforced plastic crash boxes and the behavior of each combination composed of various types of geometries and triggers under impact loading is finally researched. Chen and Ma 3 carried out the numerical simulation of the crash box based on the consideration of the strain rate of the material and found that the crash box collapse more smoothly after adding double-sided grooves at the front crash box.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that when compared with the conventional crash box, the proposed optimal design leads to great improvement on account of not only the energy absorption per unit mass, but also the initial peak force. Through adopting drop-weight impact testing, Hussain et al 2 investigated the effectiveness of disparate triggers in combination with different geometries for glass fiber reinforced plastic crash boxes and the behavior of each combination composed of various types of geometries and triggers under impact loading is finally researched. Chen and Ma 3 carried out the numerical simulation of the crash box based on the consideration of the strain rate of the material and found that the crash box collapse more smoothly after adding double-sided grooves at the front crash box.…”
Section: Introductionmentioning
confidence: 99%
“…The method of energy absorption allows monitoring the impact damage directly from the parameters acquired throughout the impact event [9][10][11][12][13]. However, it is critical to understand how the initial impact energy is introduced into the material.…”
Section: Introductionmentioning
confidence: 99%
“…The selected structures must fulfill the highest strength to weight ratio to be practical for impact applications. 1,2 Due to the practicality of cylindrical tubes in diverse industries, ranging from aerospace to automobile industry, 3,4 they have been an ongoing research topic for researchers. When it comes to choosing the suitable structure, although countless structures could be considered as an absorber, considering the structures possessing negative Poisson's ratio (NPR) behavior, so-called auxetics, 5 could be a suitable choice.…”
Section: Introductionmentioning
confidence: 99%